Livelihood transformation through pig farming among tribal communities of Jharkhand under the Farmer FIRST Programme - Bhadauria, Pragya; Kumar, Anjani; Sinha, Rekha; Yadav, V. K.; Kamal, Reena (Indian Farming, 2025)
Pig farming is an important livelihood activity for tribal and marginal farmers of Jharkhand, providing a sustainable source of income, employment, and nutrition. Among the livestock systems, pig is more efficient converter of low-quality feed to high quality animal protein and also needs less feed per kg of body weight. In Jharkhand, Farmer FIRST Programme carried out in tribal villages of Ranchidistrict shown a remarkable growth in pig-based production system towards the sustainable livelihood of the tribes. Scientifically managed pig production system along with crossbreed namely ‘Jharsuk’ can play an important role in mitigating hunger, providing nutritional security and counteracting environmental degradation in the tribal area.